무산세 열연 용융아연도금강판의 도금밀착성에 미치는 도금욕 Al농도의 영향 - 전선호; 최진원 (한국표면공학회지, 1999)
The effect was investigated that aluminium in the zinc bath has on the coating adhesion of Hot-rolled Galvanized Iron(HGI) manufactured without pickling process. It is thought that the coating adhesion of HGI manufactured without pickling process is good due to the fact that increasing aluminium content in the zinc bath makes zinc and aluminium diffuse to the cracks or pores in the scale formed through the reduction heat treatment, and Fe-Zn-Al compound with good ductility is formed in the scale layer and plays a role of anchor between zinc coating and substrate. It is possible that HGI with the good coating adhesion was produced without pickling treatment in the zinc bath with more that 3wt% of Al content even at the $550^{°}C$ of conventional reduction heating temperature. In creasing the temperature of heating section and aluminium content in the zinc bath prevents the Zn-Fe alloy. The corrosion resistance of HGI manufactured without pickling process is excellent because of the mixed reaction of zinc sacrifice and aluminium passivity film.